2011
DOI: 10.2967/jnumed.110.081620
|View full text |Cite
|
Sign up to set email alerts
|

18F-Labeled Bombesin Analog for Specific and Effective Targeting of Prostate Tumors Expressing Gastrin-Releasing Peptide Receptors

Abstract: Bombesin is a peptide exhibiting high affinity for the gastrinreleasing peptide receptor (GRPr), which is highly overexpressed on prostate cancer cells. In the present study, we developed an 18 F-labeled bombesin analog, 18 F-BAY 86-4367, which is currently being clinically tested for use in PET of prostate cancer. Methods: In vitro pharmacologic studies were performed to characterize the nonradioactive ( 19 F) standard of the bombesin analog for binding affinity and selectivity for GRPr. The stability of 18 F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
68
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 25 publications
0
68
1
Order By: Relevance
“…Other methods have also been used for radiofluorination of bombesin derivatives, notably by using N-succinimidyl-4-18 F-fluorobenzoate, 3-cyano-4-18 F-fluoro-benzoyl derivatives or fluoropyridine prosthetic groups, with variable success. [37][38][39][40] All of these methods required one or two HPLC purification steps, with lengthy radiolabeling procedures. Considering the widespread availability of 18 F, and the straightforward labeling technique using the 18 F-19 F isotope exchange reaction, 18 FAmBF 3 -MJ9 is a promising probe for non-invasive imaging of GRPR in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Other methods have also been used for radiofluorination of bombesin derivatives, notably by using N-succinimidyl-4-18 F-fluorobenzoate, 3-cyano-4-18 F-fluoro-benzoyl derivatives or fluoropyridine prosthetic groups, with variable success. [37][38][39][40] All of these methods required one or two HPLC purification steps, with lengthy radiolabeling procedures. Considering the widespread availability of 18 F, and the straightforward labeling technique using the 18 F-19 F isotope exchange reaction, 18 FAmBF 3 -MJ9 is a promising probe for non-invasive imaging of GRPR in humans.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it was demonstrated that the anti-tumor activity of GrP antagonists involves different mechanisms as the reduction of EGFR and Her2 levels, the alteration of MAPK, PKC, pAkt, and COX-2 signaling, the attenuation of c-fos and c-jun expression, the modulation of wild-type and mutated forms of p53 along with an alteration of Bcl-2/BAX ratio, the inhibition of vascular endothelial growth factor (VEGF) [47] . Radiolabeled GrP analogues represent another chance in targeting GrP receptors, thus they are currently considered promising radiopharmaceuticals for detection and treatment of different types of tumors [48,49] .…”
Section: Gpcrs Activated By Peptidesmentioning
confidence: 99%
“…However, they showed only limited success, probably because of their limited metabolic stability. Recently, the 18 F-labeled BAY 864367 was identified as a potent synthetic GRPr antagonist, and its preclinical evaluation showed specific and effective GRPr targeting in PC-3 tumor-bearing mice, with high tumor uptake, excellent tumor-to-background ratios, and, importantly, excellent metabolic stability (11). To further investigate this promising tracer, an exploratory clinical trial was performed.…”
Section: Discussionmentioning
confidence: 99%
“…The poor performance of the most commonly used tracer in cancer, 18 F-labeled glucose ( 18 F-FDG), for the detection of PCa is due to the relatively slow growth of well-differentiated PCa and consequently low glucose metabolism (3,4). This drawback has led to the development of other PET tracers such as 11 C-choline and 18 F-choline, which have been reported to be potentially useful for the detection of PCa lesions and are in routine clinical use (5)(6)(7). However, the fact that radiolabeled choline analogues cannot differentiate between benign hyperplastic prostate cells and malignant carcinoma cells may limit their diagnostic value.…”
mentioning
confidence: 99%
See 1 more Smart Citation